Utilization of computer simulation for solution of flood-control resevoir protection function - Fikejz, Jan; Roušar, Ladislav; Zachoval, Tomáš (Dime University of Genoa, 2019)
This article deals with the use of a computer simulation to solve the protective function of a flood-control reservoir as a support tool for flood wave transformation. Attention is primarily focused on the design and implementation of a simulation tool enabling to implement selected mathematical approach for numerical solution of the balance equation of inflow, outflow and retention of water in the reservoir. The designed software tool is then used for the selected experiment of transformation of theoretical flood wave by flood-control reservoir.
Využití počítačové simulace pro řešení funkce ochrany před povodněmi
Keywords: Utilization; computer; simulation; for; solution; flood-control; resevoir; protection; function; Využití; počítačové; simulace; pro; řešení; funkce; ochrany; před; povodněmi